Peran Penyuluh Pertanian Dalam Pengembangan Kelompok Tani Di Desa Penfui Timur Kecamatan Kupang Tengah Kabupaten Kupang - Sanaunu, Soni Rian; Olviana, Tomycho; Nikolaus, Serman; Levis, Leta Ravael (Undana Press, 2024)
This research was carried out in East Penfui Village, Central Kupang District, Kupang Regency in March-April 2023 with the aim of finding out the role of agricultural instructors in developing farmer groups in East Penfui Village, Central Kupang District, Kupang Regency and to find out the obstacles of agricultural instructors in the field in their activities and implementation of efforts to develop farmer groups in East Penfui Village, Central Kupang District, Kupang Regency. The choice of research location was carried out deliberately with the consideration that the village was very advanced in its agricultural extension services. The research sample was taken randomly as many as 52 members of farmer groups from a population of 111 members of farmer groups. Data were analyzed using data according to a Likert scale using average, percentage and frequency analysis. Based on the average score of the role of Agricultural Instructors in villages of Kupang Tengah District Kupang regency with the highest indicator of the role of Agricultural Instructors being educators with an everage of 3,21 and a maximum score achievement percentage of 64,13%. This value is included in “fairly good” category. While the lowest indicator of the role of Agricultural Extension officers is motivator with an average of 2,90 and a maximum score achievement presentage of 57,98%, this value is included in the “Fairly good” category. This shows that the role of agricultural instructors as educators in carrying out their role as istructors is the best. Then the obstacles that limit agricultural extension officers from playing a good role are as follows : Lack of facilities or practical materials in the field that support the smooth process of activities, Lack of farmer participation during field visits by extension workers., Farmers’ lack of understanding of directions or explanations from extension workers.